Experience in emergency management of first-episode immune thrombotic thrombocytopenic purpura over the past 21 years: a single-center retrospective study - Zhang, Liqian; Huang, Wenfeng; Yang, Fengtao; Cao, Lingjie; Shi, Maojing; Gao, Weibo; Pei, Yuanyuan; Zhu, Jihong (Frontiers in Immunology, 2026)
BackgroundImmune thrombotic thrombocytopenic purpura (iTTP) is a rare but fatal hematologic disorder characterized by thrombocytopenia, microangiopathic hemolytic anemia, and multiorgan dysfunction. Early diagnosis and prompt treatment, including plasma exchange (PE), corticosteroids, and rituximab (RTX), are critical for improving outcomes. However, real-world emergency management experiences for first-episode iTTP remain understudied.MethodsThis single-center retrospective study analyzed 96 patients with first-episode iTTP admitted to the emergency department of Peking University People’s Hospital between 2004 and 2024. Baseline characteristics, clinical features, treatment modalities, and outcomes were evaluated. Logistic and Cox regression analyses were conducted to identify predictors of clinical response and mortality.ResultsAmong the enrolled patients, the median age was 45 years and 54.2% were female. The comorbidities included rheumatologic and antoimmune diseases (28.1%) and cancer (11.5%). The mortality rate was 38.5% whereas the relapse rate was 13.6% in survival group. RTX administration increased over time (0% in 2004–2010 vs. 51.9% in 2018-2024) and was associated with improved survival (HR = 0.27, 95% CI: 0.11-0.66). Corticosteroid pulse therapy was an independent predictor of clinical response (OR = 2.8, 95% CI: 1.1-7.6). Independent predictors for mortality included age over 45 years (HR = 5.5, 95% CI: 2.1-14.3), pentad symptoms (HR = 3.5, 95% CI: 1.5-8.4), and lactate dehydrogenase over 1500 U/L (HR = 2.7, 95% CI: 1.2-5.8).ConclusionsThis study highlighted the importance of early RTX and corticosteroid pulse therapy in the emergency management of first-episode iTTP. We also provide a risk stratification framework for emergency clinicians, guiding more prompt and effective management as well as personalized therapy.